An improved analytical method for anti-uplift stability of narrow foundation pit based on energy method - Ren, Shuping; Wan, Kang; Tai, Jun; Hu, Ke; Yao, Shaonan; Cui, Deshan (Frontiers in Built Environment, 2025)
With the rapid advancement of urbanization in China, the scale of construction involving narrow trench foundation pits in municipal public utility pipeline projects has witnessed a substantial expansion. However, existing research predominantly focuses on deep and wide foundation pits, and the current stability calculation methods are not applicable to narrow trench foundation pits systems. A comprehensive approach integrating model tests, numerical simulations, and theoretical analyses were used to address this gap. Results from model tests demonstrate that the failure surface of a narrow trench presents a morphological feature notably distinct from that of wide excavations: the failure surfaces of the two sidewalls converge at the trench bottom, a characteristic pattern that diverges substantially from the assumptions inherent in traditional failure modes. Numerical simulations using finite element methods further demonstrate that soil in the active zone undergoes plastic flow around the lower edge of the supporting plate toward the passive zone, forming a coupled failure mechanism where supporting plate exerts significant squeezing forces on the passive zone soil. Building upon the clarification of the morphology and mechanism of the failure surface, an improved critical failure criterion for narrow trench foundation pits is proposed. This study derives a calculation formula for anti-uplift stability using energy method, showing that decreasing foundation pit width increases the overlapping area of sliding surfaces, thereby enhancing the components of shear stress and soil self-weight along the failure surface. This mechanism significantly improves the anti-uplift stability calculation of narrow trench foundation pit, further optimizes support structures for narrow excavations to maximize their performance, reduce costs and increase efficiency. When the width of the foundation pit decreases from 1.5 times to 0.4 times its own width, the anti-uplift stability coefficient increases from 1.97 to 3.18, representing an increase by a factor of 1.61. Consequently, it provides a theoretical foundation for the design and construction of municipal utility pipelines in urban pipeline engineering.